2011
DOI: 10.1097/mnm.0b013e32834bbda7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optimal acquisition protocol of breath-hold PET/CT for the diagnosis of thoracic lesions

Abstract: BH-PET/CT improved the misregistration between PET and CT images and increased the SUVmax of thoracic lesions. The recommended number of BH-PET images for summation with 20 s of acquisition time is three or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Liver profiles and kidney VOIs also identified characteristics of respiratory motion. On the other hand, we did not see significant change in SUV in the kidneys between gated and ungated scans, which may have been expected from analogous studies assessing lung lesions [21,34]. We suspect that kidney motion and uptake were not sufficient to show this effect.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Liver profiles and kidney VOIs also identified characteristics of respiratory motion. On the other hand, we did not see significant change in SUV in the kidneys between gated and ungated scans, which may have been expected from analogous studies assessing lung lesions [21,34]. We suspect that kidney motion and uptake were not sufficient to show this effect.…”
Section: Discussionsupporting
confidence: 50%
“…While strategies for optimized data binning have been presented [11,21], the primary efforts for full data utilization use nonlinear deformation maps to map information from different gates to a target gate, essentially recombining the gates back into a single motion-free frame with high resolution and high count statistics [22-24]. Limitations of these techniques are that they can be complex, parameter and distribution dependent, prone to error, difficult to fully characterize, and some require heavy processing [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In the histograms, the peaks were broad and unclear because of the smearing of radioactivity due to respiratory motion. The peaks could not be separated from each other and thus the resulting CSH curves of the 3 phantoms showed a similar pattern [12,13,17]. In the fractal analysis, the FDs of the HO and HE1 phantoms did not differ from each other and were smaller than that of the HE2 phantom.…”
Section: Discussionmentioning
confidence: 94%
“…Although these methods have been reported to be useful for the evaluation of malignant tumors in the clinical setting [6,7], it has been suggested that factors such as partial volume effect (PVE) and image noise may influence the results [7]. In lung cancer, respiratory motion causes the deterioration of image quality and reduces FDG uptake due to image blurring [12,13]. It is, therefore, possible that respiratory motion influences the results of analyses for the intratumoral heterogeneity of 18 F-FDG uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Several bhPET studies have focused on lung carcinoma, but only a few have addressed abdominal diseases, and—to our knowledge—none has explicitly reported on melanoma lesions. Also, all available studies describe SUV max as quantitative marker, [10,14,15] but only a few mention the metabolic volume [10,1618] or the SUV mean . [10] In chest lesions, for example, the SUV max at bhPET has proven 32.5% higher than at fbPET.…”
Section: Discussionmentioning
confidence: 99%